2012
DOI: 10.1111/j.1461-0248.2012.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Host phylogeny and specialisation in parasitoids

Abstract: The host range of insect parasitoids and herbivores is influenced by both preference-related traits which mediate host choice behaviour, and performance-related traits which mediate the physiological suitability of the consumer-resource interaction. In a previous study, we characterised the influence of preference- and performance-related traits on the host range of the aphid parasitoid Binodoxys communis (Hymenoptera: Braconidae) and herein we build upon those data sets by mapping a series of these traits ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…It has been shown that Trichogramma parasitoids prefer hosts with relatively big eggs [34] but the eggs of T. absoluta are, by comparison, three times smaller than the eggs of E. kuehniella used in the rearing. Furthermore, we found a positive relationship between the number of parasitized eggs and the proportion of females accepting T. absoluta as host, demonstrating that parasitism levels were directly linked to the willingness of females to attack the host (as demonstrated in other parasitoid systems [25], [32], [35], [36]). Second, low parasitism may result not only from rejection of T. absoluta eggs as host but rather from the poor capacity of some Trichogramma species/strains to cope with specific tomato plant characteristics.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been shown that Trichogramma parasitoids prefer hosts with relatively big eggs [34] but the eggs of T. absoluta are, by comparison, three times smaller than the eggs of E. kuehniella used in the rearing. Furthermore, we found a positive relationship between the number of parasitized eggs and the proportion of females accepting T. absoluta as host, demonstrating that parasitism levels were directly linked to the willingness of females to attack the host (as demonstrated in other parasitoid systems [25], [32], [35], [36]). Second, low parasitism may result not only from rejection of T. absoluta eggs as host but rather from the poor capacity of some Trichogramma species/strains to cope with specific tomato plant characteristics.…”
Section: Discussionsupporting
confidence: 65%
“…The low parasitism recorded for some strains may be attributed to two factors. First, in parasitoids, host specificity is mediated in part by host recognition and acceptance by the adult female parasitoid [25], [32], [33]. It has been shown that Trichogramma parasitoids prefer hosts with relatively big eggs [34] but the eggs of T. absoluta are, by comparison, three times smaller than the eggs of E. kuehniella used in the rearing.…”
Section: Discussionmentioning
confidence: 99%
“…This principle is well accepted and tested in weed biological control [80,81]. Insect biological control is complicated by an extra trophic level (host food plant), not to mention the much larger number of potential non-target hosts, and although studies have shown that host phylogeny is often a strong factor in host selection by parasitoids and indeed parasitoid performance in a host (e.g., [82]), host ecology can also be a determinant of host selection. For example, host use by parasitoids of leaf-mining insects was shown to be capable of spanning several orders of insects [83].…”
Section: Discussionmentioning
confidence: 99%
“…When considering Aphidiine parasitoids, L. japonica proved to be a key natural enemy of cotton aphid in Northern China [44], [48]. This species is also a natural enemy of phylogenetically closely related aphid species [49] e.g. the soybean aphid Aphis glycines Matsumura in Japan and Indonesia [50] and the brown citrus aphid Toxoptera citricida Kirkaldy [51], [52].…”
Section: Discussionmentioning
confidence: 99%